The Effectiveness Of Role-Play Technique In Teaching Speaking at MTs Al-Hadari An-Nawawi Kubu Raya - Akhdan Naufal; Alvina Yolanda; Dewi Ismu Purwaningsih (Nusantara Journal of Multidisciplinary Science, 2025)
This study aims to determine the effect of Role-play Technique in Teaching Speaking. The research design used is a Dependent sample t-test, while the research method is quantitative with the role-play technique as the independent variable (X) while teaching speaking as the dependent variable (Y). The participants in this study were all 15 students of Mts Al-Hadari An-Nawawi Kubu Raya, the data in the study were collected using an instrument (oral test), and then normality test, homogeneity test, and descriptive statistics were used to evaluate the requirements of data analysis. The dependent t-test analysis was used to test the hypothesis using computer software assistance through the SPSScversion 22 for the Windows program. Based on the research findings and discussion, the following conclusions can be drawn: There is an effect of using role-play technique in teaching speaking in Mts Al-Hadari An-Nawawi Kubu Raya. This is indicated by the t-test result, which is t-count is (-16.102) > t-table (1.761). With a significance level of 0.05. This shows that there is a positive effect of using role-play technique in teaching speaking, this means Ha is accepted and Ho is rejected.